The Hordaland Women's Cohort: A prospective cohort study of incontinence, other urinary tract symptoms and related health issues in middle-aged women - Hunskaar Steinar; Qureshi Samera; Jahanlu David (BMC, 2008)
Abstract Background Urinary incontinence (UI) is a prevalent symptom in middle-aged women, but data on incidence is limited and rarely reported. In order to analyze incidence, remission, or development patterns of severity and types of UI, we have established a 15-year prospective cohort (1997-2012). Methods The Cohort is based on the national collection of health data gathered from county studies (CONOR). Hordaland Health Study (HUSK) is one of them from Hordaland County. Each of the county studies may have local sub-studies and our Cohort is one of them. The Cohort included women aged 40-45 in order to have a broad approach to women's health including UI and other lower urinary tract symptoms (LUTS). A onefifth random sampling from HUSK was used to create the Cohort in 1997-1999. For the necessary sample size a preliminary power calculation, based on a 70% response rate at inclusion and 5% annual attrition rates was used. The Cohort is planned to collect data through questionnaires every second year for the 15-year period from 1997-2012. Discussion The Cohort represents a relatively large random sample (N = 2,230) of about 15% of the total population of women born between 1953-57 in the county of Hordaland. Our data shows that the cohort population is very similar to the source population. The baseline demographic, social and medical characteristics of the Cohort are compared with the rest of women in HUSK (N = 7,746) and there were no significant differences between them except for the level of education (P = 0.001) and yearly income (P = 0.018), which were higher in the Cohort population. Urological characteristics of participants from the Cohort (N = 1,920) were also compared with the other participants (N = 3,400). There were no significant statistical differences except for somewhat more urinary continence (P = 0.04), more stress incontinence (P = 0.048) and smaller amount of leakage (P = 0.015) in the Cohort. In conclusion, the Cohort ispopulation-based, with little selection bias, and thus is a rather unique study forinvestigating UI and LUTS in comparison with many other projects with similar purposes.